Parsing TTree Formula in Python - Roy, Aryan; Pivarski, Jim (EPJ Web of conferences, 2025)
Uproot can read ROOT files directly in pure Python but cannot (yet) compute expressions in ROOT’s TTreeFormula expression language. Despite its popularity, this language has only one implementation and no formal specification. In a package called “formulate,” we defined the language’s syntax in standard BNF and parse it with Lark, a fast and modern parsing toolkit in Python. With formulate, users can now convert ROOT TTreeFormula expressions into NumExpr and Awkward Array manipulations. In this contribution, we describe BNF notation and the Look Ahead Left to Right (LALR) parsing algorithm, which scales linearly with expression length. We also present the challenges with interpreting TTreeFormula expressions as a functional language; some function-like forms can’t be expressed as true functions. We also describe the design of the abstract syntax tree that facilitates conversion between the three languages. The formulate package has zero package dependencies, so we are adding it as one of Uproot’s dependencies so that Uproot will be able to use TTreeFormula expressions, whether they are hand-written or embedded in a ROOT file as TTree aliases.